Targeting Selectins Mediated Biological Activities With Multivalent Probes - Ganesh, Deepak; Jain, Prashant; Shanthamurthy, Chethan Devanur; Toraskar, Suraj; Kikkeri, Raghavendra (Frontiers in Chemistry, 2021)
Selectins are type-I transmembrane glycoproteins that are ubiquitously expressed on activated platelets, endothelial cells, and leukocytes. They bind to cell surface glycoproteins and extracellular matrix ligands, regulate the rolling of leukocytes in the blood capillaries, and recruit them to inflammatory sites. Hence, they are potential markers for the early detection and inhibition of inflammatory diseases, thrombosis, cardiovascular disorders, and tumor metastasis. Fucosylated and sialylated glycans, such as sialyl Lewisx, its isoform sialyl Lewisa, and heparan sulfate, are primary selectin ligands. Functionalization of these selectin-binding ligands on multivalent probes, such as nanoparticles, liposomes, and polymers, not only inhibits selectin-mediated biological activity but is also involved in direct imaging of the inflammation site. This review briefly summarizes the selectin-mediated various diseases such as thrombosis, cancer and recent progress in the different types of multivalent probes used to target selectins.